New concepts for translational head and neck oncology: lessons from HPV-related oropharyngeal squamous cell carcinomas - Kostareli, Efterpi; Holzinger, Dana; Heß, Jochen (Frontiers in oncology, 2012)
Human papillomavirus (HPV) infection is well established as etiological agent responsible for a number of pathologies affecting the stratified epithelia of skin and anogenital sites. More recently, the infection by (mucosal) high-risk HPV types has also been found to be causally associated with squamous cell carcinoma in the head and neck region (HNSCC), especially in the oropharynx. Intriguingly, HPV-related oropharyngeal squamous cell carcinomas (OPSCC) represent a distinct clinical entity compared to HPV-negative tumors with regard to treatment response and survival outcome, and the association between HPV infection and OPSCC has potential important implications for prevention and treatment decision making. The improved survival of patients with HPV-related tumors also raises the question, whether a better understanding of the underlying differences may guide us to identify new therapeutic concepts that could be used in targeted therapy for HPV-negative and improved therapy for HPV-positive cancers, and finally to initiate individualization of treatment based on the biology of OPSCC. This review summarizes the most recent advances in our understanding of the molecular principles of HPV-related OPSCC mainly based on functional genomic approaches, but also emphasizes the significant role played by the tumor microenvironment, especially the immune system, for improved clinical outcome and differential sensitivity of HPV-related tumors to current treatment options.
Gesehen am 05.11.2018